Countercyclical prudential buffers and bank risk-taking - Illueca, Manuel; Norden, Lars; Pacelli, Joseph; Udell, Gregory F. (Journal of Financial Intermediation, 2022)
We investigate the effects of countercyclical prudential buffers on bank risk-taking. We exploit the introduction of dynamic loan loss provisioning in Spain, mandating that banks use historical average loss rates in their estimation of loan loss provisions. We find that dynamic loan loss provisioning is associated with reductions in timely loan loss provisioning. Banks that previously recognized loan losses in a timely fashion exhibit the greatest reductions in timeliness and consequently extend loans to riskier borrowers with lower accounting quality. Our results have policy implications for the debate on the use of financial reporting requirements in mitigating capital pro-cyclicality.